Proposal for rational antibacterial use in the diagnosis and treatment of dogs with chronic diarrhoea. (17th February 2020) - Cerquetella, M.; Rossi, G.; Suchodolski, J. S.; Schmitz, S. Salavati; Allenspach, K.; Rodríguez‐Franco, F.; Furlanello, T.; Gavazza, A.; Marchegiani, A.; Unterer, S.; Burgener, I. A.; Pengo, G.; et al.
Abstract : Chronic diarrhoea is a frequent complaint in canine practice and the diagnostic path is often characterised by numerous diagnostic tests and stepwise empirical treatments, often applied before gastrointestinal endoscopy/mucosal biopsies. These include dietary interventions (novel protein, hydrolysed protein diet), parasiticides and still, in many cases, antibacterials. Indiscriminate use of antibacterial drugs risks detrimental consequences for both the individual patient (antimicrobial resistance, long‐term disruption of intestinal bacterial populations, potential worsening of gastrointestinal signs) and the general public. For that reason, in this Perspective essay we advocate use of antibacterials only after histopathologic evaluation of gastrointestinal biopsies or, for those cases in which endoscopy is not possible, after other therapeutic trials, such as diet/pre‐probiotics or anti‐inflammatory drugs have proven unsuccessful. They should be reserved, after appropriate dietary trials, for those canine chronic diarrhoeic patients with signs of true primary infection ( i.e. signs of systemic inflammatory response syndrome or evidence of adherent‐invasive bacteria) that justify antibacterial use.